Beyond vision: Exploring the impact of visual perception on participation in children with autism spectrum disorder - Sümeyye Belhan Çelik; Esma Özkan (PLoS ONE, 2025)
Visual perception plays a crucial role in the daily participation of children with Autism Spectrum Disorder (ASD) in everyday activities. Exploring the relationship between visual perception skills and participation levels can provide valuable insights into effective intervention strategies to enhance engagement in various settings. This study aimed to evaluate visual perception and participation levels in children with ASD in terms of demographic variables and to examine the relationships between visual perception skills and participation in daily life activities. Sixty-one children with autism (mean age = 8.21 ± 1.05 years) enrolled in a special education center were assessed using the Motor-Free Visual Perception Test – 4 (MVPT-4) for visual perception and the Child and Adolescent Scale of Participation (CASP) for participation levels across home, school, neighborhood, and community settings. Statistical analyses included correlation and regression analyses to examine relationships between variables. Findings indicated that boys participated more in home and school activities, whereas girls were more engaged in community settings. Additionally, children from nuclear families had higher participation levels than those from separated families. Regression analysis indicated that visual perception was strongly associated with participation levels (β = 0.617, p < 0.001), accounting for 55.8% of the variance in CASP Total scores. A significant positive correlation was found between visual perception and participation in home (r = 0.358, p < 0.001), school (r = 0.313, p = 0.014), and community activities (r = 0.361, p = 0.004), suggesting that better visual perception is linked to higher participation levels. The results suggest that visual perception is a significant factor influencing participation levels in children with ASD. Furthermore, family type showed a significant contribution to participation variance in the regression analysis. These findings underscore the importance of incorporating visual perception-based interventions to enhance the participation of children with ASD in everyday activities, yet they should be interpreted as correlational rather than causal, highlighting the need for future longitudinal or interventional research.